Manajemen Pendidikan Kewirausahaan dalam Menumbuhkan Semangat Kemandirian Siswa Kelas XIIdi SMK Hidayatuzzu’ama - Akbar, M. Syahid; Agussalim, Agussalim; Purwandari, Elce (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the management of entrepreneurship education in fostering a spirit of independence among 12th-grade students at Hidayatuzzu'ama Vocational High School in Tungkal Jaya District. This study used a qualitative approach with a case study method. Data were obtained through interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and drawing conclusions. The results indicate that the management of entrepreneurship education at Hidayatuzzu'ama Vocational High School includes three main stages: (1) structured planning through the development of a practice-based curriculum, teacher training, and the establishment of an entrepreneurial culture within the school environment; (2) implementation focused on project-based learning and hands-on practice that encourages students to be creative and take responsibility for the results of their efforts; and (3) periodic evaluation using the CIPP model to assess the context, input, process, and product of learning. Factors supporting the program's success include the principal's commitment, the active role of teachers as facilitators, student enthusiasm, and school facilities. Inhibiting factors include limited capital, production facilities, and market access.   Keywords: Educational Management, Entrepreneurship, Student Independence, Project-Based Learning